Business Ethics in Harmonization of Society Life - Ярослав Мартинишин; Олена Хлистун; Марина Антонівська; Оксана Крупа (Socio-Cultural Management Journal, 2022)
Introduction.Business ethics is one of the most pressing problems for societies with a developed market economy. Its emergence is driven by the growing influence of business on political, economic, and socio-cultural processes, the vector of which is not necessarily favorable for humanity, especially today, when business is moving to the global level, and national social structures remain at the local level. Purpose and methods. The purpose of the article is to substantiate the theoretical principles of business ethics in the organization of society life, the use of which will provide an opportunity to integrate into the system of public and private administrationof the ethical component and, on this basis, to harmonize the relationship betweenbusiness and society. The methodological basis of the study is the dialectical principleof cognition, systemic, historical, and cultural approaches to the study of the interactionbetween business and society. Results. The socio-cultural sources, content, and formsof business ethics of “Service” are clarified: charity, philanthropy, economic development. The content of business ethics “Social Responsibility”, the scope and forms of its application, and current problems of ethical control have been determined. The moral prerequisites and ethical dimensions of business life are established, and the ways of maintaining business ethics in society are substantiated. Conclusions. The scientific novelty of the research results lies in the systemic and cultural deepening of theunderstanding of the essence, role, and importance of business ethics in the organization of society life. The significance of the study is revealed in the addition of science to new theoretical provisions on business ethics, as well as the possibility of using them in the process of training entrepreneurs and managers of business organizations.